Dissecting human haematopoietic progenitors - Samitsch, M (2013)
Human haematopoiesis resembles a complex hierarchy, however most intermediate stages are only poorly defined. Efforts to characterise human progenitors have been inconsistent and failed to integrate previous knowledge. Furthermore, characterisation of normal progenitors has important implications in acute myeloid leukaemia (AML) biology. We previously established that leukaemic stem cells (LSCs) resemble the immunophenotypic progenitor compartments more closely than the stem cell fraction. Therefore, I set out to characterise human stem and progenitor cells (HSCPs) on phenotypic, molecular and functional level to complete the picture of human haematopoiesis. I purified HSPCs based on their immunophenotype from adult bone marrow (BM) and umbilical cord blood (CB) to investigate steady state and neonatal haematopoiesis. To define differentiation potentials, HSPCs were subjected to functional in vitro assays on bulk and clonal level. Limit dilution assays were used to determine the frequency of cells with multiple differentiation potentials. RNA sequencing revealed underlying lineage priming and specific gene expression signatures. I successfully characterized the incompletely defined Lin-CD34+CD38-CD45RA+ fraction in BM and CB, containing a CD10lo lymphoid-primed multipotent progenitor (LMPP) with T cell, B cell, NK cell, granulocytic and monocytic differentiation potential, and succeeded in placing it in the haematopoietic hierarchy with relation to similar lympho-myeloid progenitors defined by other groups. This research lays the foundation to characterise early human progenitors with a comprehensive toolkit on a phenotypic, molecular and functional level. Findings from this thesis might provide knowledge about potential targets in LSCs.